Deposition and application of a Mo–N back contact diffusion barrier yielding a 12.0% efficiency solution-processed CIGS solar cell using an amine–thiol solvent system. Issue 12 (7th March 2019) - Uličná, Soňa; Arnou, Panagiota; Abbas, Ali; Togay, Mustafa; Welch, Liam M.; Bliss, Martin; Malkov, Andrei V.; Walls, John M.; Bowers, Jake W.
Abstract : The use of a Mo–N barrier for solution-processed CIGS results in reduced MoSe2 formation. This enabled longer selenization time, enhanced grain growth and performance. Abstract : Delamination and high series resistance due to excessively thick MoSe2 are commonly found in solution-processed CIGS solar cells. This work shows the effective functionality of Mo–N as a back contact barrier against selenium diffusion during high temperature selenization. Mo–N barrier layers are deposited by reactive D.C. magnetron sputtering. The Mo–N barrier layer significantly reduces MoSe2 formation at the Mo/CIGS interface and consequently improves adhesion properties and enhances crystallinity of the CIGS absorber. The power conversion efficiency (PCE) of a spray-coated diamine–dithiol based CIGS solar cell improved from our previously published 9.8% to 12.0% after application of the Mo–N back contact barrier layer.